“Evaluación de maices sintéticos (zea mays)tropicales de grano amarillo en la zona del bajo mayo” - Villacorta Vásquez, .Juvenal (2003)
The present investigation work was carried out with the objective of to evaluate the synthetic yield of 18 varieties and to carry out the economic analysis in the Experimental Station El Porvenir, Juan Guerra, Country and Region San Martín. Geographically Longitude West is located with 76° 5 ', 06° 35 'of South Latitude and 330 m.s.n.m.m. The floor was of loamy texture with pH 7. the statistical design DBCR was u sed, with 20 treatments and 3 repetitions. The variety TAKFA S9624 reported the highest yield with 4.59 t/ha with a net utility of S /. 429.22 new suns, representing a relationship beneficent cost of 1.31. The ~,' variety S99TL YQ reported the biggest plant height with 221.70 cm and the var~ety S0128 bigger ear height with 125 cm. The plant aspect and ear aspect varied among good to regulate and the ear covering went of excellent to regulate, having to the varieties of synthetic corn T15 (TAKFA S9624) and T13 (S97TLY GH TO and B) with characteristic of jagged grains. The masculine flowering in the varieties of synthetic corn S0136 and COTAXTLA S96271 was late and the variety SOOTL YQ - AB like late semi . Likewise in the feminine one the variety S0136 demonstrated to be the latest, comparatively with the variety S99TL YQ-AB reported late semi. All the varieties of synthetic corns showed characteristic genotipic of moderate resistance to the one it flattens or lying.